2020
DOI: 10.1101/2020.02.24.960922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bilateral Alignment of Receptive Fields in the Olfactory Cortex

Abstract: While olfactory sensory neurons expressing the same receptor in the nose converge to the same location in olfactory bulb, projections from the olfactory bulb to the cortex exhibit no recognizable spatial topography. This lack of topography is thought to carry over for interhemispheric connectivity, which originates cortically. If connections to and within the cortex are random, information reaching a cortical neuron from both nostrils will be uncorrelated. Instead, we found that the odor responses of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…This result is inline with the indirect pathway. However, a very recent study found that a substential number of AON and aPC neurons responded to ipsi-and contralateral odors and that these responses are of similar magnitute 87 . This similarity in bilateral odor receptive fields suggests that AON and aPC neurons receive contra-input through the direct pathway.…”
Section: Functional Bilateral Connectivitymentioning
confidence: 97%
See 1 more Smart Citation
“…This result is inline with the indirect pathway. However, a very recent study found that a substential number of AON and aPC neurons responded to ipsi-and contralateral odors and that these responses are of similar magnitute 87 . This similarity in bilateral odor receptive fields suggests that AON and aPC neurons receive contra-input through the direct pathway.…”
Section: Functional Bilateral Connectivitymentioning
confidence: 97%
“…3). The exisitance of extensive bilateral connections suggests that the direct pathway plays an important role in bilateral information transfer 87 . Random connectivity between OB and OC neurons 10-12 makes the task of achieving perceptual unity more difficult.…”
Section: How Is Perceptual Unity Achieved In Olfaction?mentioning
confidence: 99%
“…Early work in anesthetized rats has shown that odor responses in PC can be nostril-specific 21 , suggesting that a given odorant may activate different neurons across PC depending on stimulus laterality. Recent work in awake mice has found that neural population responses to ipsilateral versus contralateral odorants were indeed distinguishable but remained highly correlated 22 . Our results are consistent with these rodent studies, and together suggest that ipsilateral and contralateral odors activate partially overlapping but distinct ensembles of neurons that ultimately give rise to similar yet distinguishable response dynamics at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise the intriguing possibility that the same odor delivered to the ipsilateral versus contralateral nostril may ultimately elicit similar representations that are merely shifted in time. Indeed, work in rodents has shown that PC responses to ipsilateral versus contralateral odors are correlated at the neural population level 22 .…”
Section: Ipsilateral and Contralateral Odors Elicit Similar Yet Disti...mentioning
confidence: 99%
“…In these models, the random connectivity is a necessary basis for learning arbitrary stimulus combinations during an individual’s lifetime. It remains, however, unclear whether random connectivity alone can account for specific olfactory percepts and actions, reproducible between individuals 30, 53 . Furthermore, identifying structure in the connectivity of the olfactory system has been impeded by the scarcity of single cell connectivity data available.…”
Section: Mainmentioning
confidence: 99%